"Kiev case": corruption in the Ukrainian police at the mid 1920’s - Mikheyeva, Oksana (Skhid, 2013)
The article deals with the study of specific aspects of daily life of management and ordinary workers of the Ukrainian police at the mid 1920’s based on the much-discussed in the press "Kievcase". This case was about systematic bribery in Ukrainian police (in modern language - about corruption). In this way we have detected the conditions, causes and mechanisms of the corruption that matter for the modern study of this phenomenon.